2015
DOI: 10.1007/s12035-015-9502-x
|View full text |Cite
|
Sign up to set email alerts
|

Acyl Ghrelin Improves Synapse Recovery in an In Vitro Model of Postanoxic Encephalopathy

Abstract: Comatose patients after cardiac arrest have a poor prognosis. Approximately half never awakes as a result of severe diffuse postanoxic encephalopathy. Several neuroprotective agents have been tested, however without significant effect. In the present study, we used cultured neuronal networks as a model system to study the general synaptic damage caused by temporary severe hypoxia and the possibility to restrict it by ghrelin treatment. Briefly, we applied hypoxia (pO2 lowered from 150 to 20 mmHg) during 6 h in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 71 publications
1
13
0
Order By: Relevance
“…Ghrelin has been shown to exert neuroprotection via attenuation of oxidative stress [ 41 ], blockade of apoptosis [ 18 ], and stimulation of synaptic plasticity [ 46 ]. Suda et al [ 47 ] have suggested that defective GHSR1 activity of dopaminergic neurons causes marked motor impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Ghrelin has been shown to exert neuroprotection via attenuation of oxidative stress [ 41 ], blockade of apoptosis [ 18 ], and stimulation of synaptic plasticity [ 46 ]. Suda et al [ 47 ] have suggested that defective GHSR1 activity of dopaminergic neurons causes marked motor impairment.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of both pre- and post-synaptic genes is altered by hypoxia (Curristin et al, 2002; Milash et al, 2016). Cell culture experiments using mouse hippocampal neurons show that hypoxia causes a reduction in dendritic spine numbers and impairs synaptic activity (Segura et al, 2016), as well as a persistent decline in synapse numbers (Stoyanova et al, 2016; le Feber et al, 2018). However, these studies were performed on neurons from mature animals, so whether the findings can be extrapolated to synaptic changes during embryonal development is unknown.…”
Section: Effects Of Hypoxia On Connectivity Developmentmentioning
confidence: 99%
“…Moreover, studies have revealed an association between ghrelin and neural function. Previous in vitro studies have demonstrated that ghrelin treatment enhances the synaptic density of dissociated cortical neurons with decreased synapses induced by hypoxia [ 28 ], attenuates oxygen/glucose deprivation-induced apoptosis in hypothalamic neurons [ 29 ], increases the proliferation of hippocampal neural stem cells via multiple signaling pathways [ 30 ], prevents apoptosis signal-regulating kinase 1-mediated apoptosis of rat pheochromocytoma (PC12) cells by increasing heat-shock protein 70 levels [ 31 ], and inhibits the increment of inflammatory cytokines induced by fibrillar Aβ in mice microglial cells [ 32 ]. Consistent with the in vitro studies, ghrelin has protective effects on the CNS in vivo.…”
Section: Introductionmentioning
confidence: 99%